Nanoscale refractory high-entropy alloy powder and method of making same

CN118321567BActive Publication Date: 2026-10-16NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410462378.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-17
Publication Date
2026-10-16
Estimated Expiration
2044-04-17

AI Technical Summary

Technical Problem

最常用的制备方法是熔炼,但一般需要明显较高的温度,而且一些熔点高的元素难以熔化或原子扩散缓慢,导致明显的元素偏析、气孔和残余应力等缺陷

Benefits of technology

[0020]1. This invention first forms tungsten-molybdenum precursor powder by adding acid to a combination of tungsten salt and molybdenum salt, and forms tantalum-niobium precursor powder by adding ammonia to a combination of tantalum salt and niobium salt. Then, tungsten-molybdenum composite oxide powder and tantalum-niobium composite oxide powder are prepared by heating respectively. This ensures that the tungsten-molybdenum composite oxide powder and tantalum-niobium composite oxide powder are fully in contact after subsequent magnesothermic reduction, reducing the diffusion distance and heat energy required for the alloying of the four metal elements. This ensures that nanoscale WMoTaNb refractory high-entropy alloy powder is formed after the magnesothermic reduction reaction.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a nanoscale refractory high-entropy alloy powder and a preparation method thereof, and the method comprises the following steps: firstly, dissolving ammonium paratungstate and ammonium molybdate in deionized water and then adding strong acid to obtain tungsten-molybdenum precursor powder; secondly, dissolving tantalum chloride and niobium chloride in anhydrous ethanol and then adding ammonia water to obtain tantalum-niobium precursor powder; thirdly, heating the tungsten-molybdenum precursor powder to obtain tungsten-molybdenum composite oxide powder; fourthly, heating the tantalum-niobium precursor powder to obtain tantalum-niobium composite oxide powder; and fifthly, carrying out magnesium hot reduction reaction on the tungsten-molybdenum composite oxide powder, the tantalum-niobium composite oxide powder, magnesium powder and sodium chloride; and the refractory high-entropy alloy powder is a WMoTaNb alloy single phase. The magnesium hot reduction reaction is carried out after the precursor powder and the composite oxide powder are prepared by grouping and then mixed, so that the powders are fully contacted, the diffusion distance and heat energy required for alloying of the four metal elements are reduced, the nanoscale refractory high-entropy alloy powder is ensured to be formed, and the application is suitable for the field of powder metallurgy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of powder metallurgy technology, specifically relating to a nanoscale refractory high-entropy alloy powder and its preparation method. Background Technology

[0002] High-entropy alloys are typically composed of four or more main elements with equal or similar atomic fractions, exhibiting four core effects: high-entropy effect, hysteresis diffusion effect, lattice distortion effect, and "cocktail" effect. Through rational composition design and preparation techniques, high-entropy alloys can form simple microstructures and exhibit excellent properties, such as high hardness, high strength, resistance to high-temperature softening, and good wear and corrosion resistance. Among them, refractory high-entropy alloys composed of refractory metal elements (such as V, Nb, Ta, Mo, W, Ti, Zr, Re, Cr, and Hf) exhibit very high melting points and excellent properties at high temperatures, making them potential high-temperature structural materials for industrial applications.

[0003] The preparation of refractory high-entropy alloys presents a significant challenge due to the relatively high melting points and significant differences among their constituent elements. The most common preparation method is melting, but this generally requires considerably high temperatures, and some high-melting-point elements are difficult to melt or diffuse slowly, leading to defects such as significant elemental segregation, porosity, and residual stress. Refractory high-entropy alloys prepared by vacuum arc melting have coarse grain sizes (100 μm–300 μm), which is detrimental to the grain boundary strengthening effect. Furthermore, most refractory high-entropy alloys exhibit high brittleness at room temperature, making them difficult to process into the desired shapes.

[0004] Unlike casting, powder metallurgy allows for low-temperature sintering, effectively suppressing component segregation and ultimately yielding refractory high-entropy alloys with a homogeneous phase structure. Furthermore, powder metallurgy offers significant advantages in manufacturing irregularly shaped parts, substantially improving material utilization and reducing costs. Therefore, powder metallurgy has become a highly promising and promising option for preparing refractory high-entropy alloys.

[0005] With the rapid development of high-temperature technology, the performance requirements for structural materials are becoming increasingly stringent. Preparing stronger, higher-performance refractory high-entropy alloys to ensure reliability under extreme service conditions has become an important research direction. Therefore, exploring a reasonable and efficient method to successfully prepare a nanoscale refractory high-entropy alloy powder has significant theoretical and practical application value. Summary of the Invention

[0006] The technical problem to be solved by this invention is to provide a method for preparing nanoscale refractory high-entropy alloy powder, addressing the shortcomings of the prior art. This method involves preparing tungsten-molybdenum precursor powder by adding acid to tungsten and molybdenum salts, and preparing tantalum-niobium precursor powder by adding ammonia to tantalum and niobium salts. Then, tungsten-molybdenum composite oxide powder and tantalum-niobium composite oxide powder are prepared by heating respectively. Magnesium powder and sodium chloride are then added to carry out a magnesothermic reduction reaction, ensuring sufficient contact between the powder elements. This reduces the diffusion distance and heat energy required for the alloying of the four metal elements, thereby guaranteeing the formation of nanoscale WMoTaNb refractory high-entropy alloy powder, suitable for preparing refractory high-entropy alloys with high strength and toughness.

[0007] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is: a method for preparing nanoscale refractory high-entropy alloy powder, characterized in that the method includes the following steps:

[0008] Step 1: Preparation of tungsten-molybdenum precursor powder: Under the condition of electromagnetic stirring in a water bath, ammonium paratungstate and ammonium molybdate are dissolved simultaneously in deionized water to obtain a mixed solution. Then, strong acid is added to the mixed solution until precipitation is complete. After removing the supernatant, the solution is dried to obtain tungsten-molybdenum precursor powder.

[0009] Step 2: Preparation of tantalum-niobium precursor powder: Under the condition of electromagnetic stirring in a water bath, tantalum chloride and niobium chloride are dissolved simultaneously in anhydrous ethanol to obtain a mixed solution. Then, ammonia water is added to the mixed solution until precipitation is complete. After removing the supernatant, the solution is dried to obtain tantalum-niobium precursor powder.

[0010] Step 3: Preparation of tungsten-molybdenum composite oxide powder: The tungsten-molybdenum precursor powder prepared in Step 1 is heated and kept at a constant temperature in air and then cooled in a furnace to obtain tungsten-molybdenum composite oxide powder.

[0011] Step 4: Preparation of tantalum-niobium composite oxide powder: The tantalum-niobium precursor powder prepared in step 2 is heated and kept at a constant temperature in air and then furnace cooled to obtain tantalum-niobium composite oxide powder.

[0012] Step 5, Magnesium reduction reaction: The tungsten-molybdenum composite oxide powder prepared in step 3 and the tantalum-niobium composite oxide powder prepared in step 4 are uniformly mixed with magnesium powder and sodium chloride. The mixture is heated and kept at a constant temperature under argon atmosphere to carry out the magnesium reduction reaction. After furnace cooling, the product is dissolved with strong acid and allowed to stand to precipitate. After removing the supernatant, it is dried to obtain nano-sized WMoTaNb refractory high entropy alloy powder.

[0013] The above-mentioned method for preparing nanoscale refractory high-entropy alloy powder is characterized in that, in step one, the temperature of the water bath electromagnetic stirring condition is 60°C, and the mixed solution is prepared according to the ratio of 5g to 20g of ammonium paratungstate and 5g to 20g of ammonium molybdate simultaneously dissolved in 130mL to 280mL of deionized water; in step two, the temperature of the water bath electromagnetic stirring condition is 60°C, and the mixed solution is prepared according to the ratio of 1g to 10g of tantalum chloride and 1g to 10g of niobium chloride simultaneously dissolved in 50mL to 110mL of anhydrous ethanol.

[0014] The above-mentioned method for preparing nanoscale refractory high-entropy alloy powder is characterized in that the mass of ammonium paratungstate and ammonium molybdate in step one and tantalum chloride and niobium chloride in step two satisfy: 1.3[ammonium paratungstate] + 4.2[ammonium molybdate] = (3.4~8.3)([tantalum chloride] + [niobium chloride]).

[0015] The above-mentioned method for preparing nanoscale refractory high-entropy alloy powder is characterized in that the heating and holding temperature in step three is 200℃~600℃ and the time is 0.5h~5h; the heating and holding temperature in step four is 700℃~1000℃ and the time is 0.5h~5h.

[0016] The above-mentioned method for preparing nanoscale refractory high-entropy alloy powder is characterized in that, in step five, the mass of magnesium powder is 5 to 11 times the total mass of tungsten-molybdenum composite oxide powder and tantalum-niobium composite oxide powder, and the mass of sodium chloride is 1.5 to 4.5 times the mass of magnesium powder.

[0017] The above-mentioned method for preparing nanoscale refractory high-entropy alloy powder is characterized in that the magnesium thermal reduction reaction in step five is carried out at 1000℃~1200℃ for 2h~8h.

[0018] Meanwhile, the present invention also discloses a nanoscale refractory high entropy alloy powder prepared by the above method, characterized in that the particle size of the nanoscale refractory high entropy alloy powder is 10nm to 180nm, the average particle size is 30nm to 80nm, the microstructure is a WMoTaNb alloy single phase, and the atomic percentages of W, Mo, Ta and Nb are 20% to 60%, 20% to 60%, 8% to 35%, and 8% to 35%, respectively.

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] 1. This invention first forms tungsten-molybdenum precursor powder by adding acid to a combination of tungsten salt and molybdenum salt, and forms tantalum-niobium precursor powder by adding ammonia to a combination of tantalum salt and niobium salt. Then, tungsten-molybdenum composite oxide powder and tantalum-niobium composite oxide powder are prepared by heating respectively. This ensures that the tungsten-molybdenum composite oxide powder and tantalum-niobium composite oxide powder are fully in contact after subsequent magnesothermic reduction, reducing the diffusion distance and heat energy required for the alloying of the four metal elements. This ensures that nanoscale WMoTaNb refractory high-entropy alloy powder is formed after the magnesothermic reduction reaction.

[0021] 2. This invention controls the addition of ammonium paratungstate, ammonium molybdate, tantalum chloride, and niobium chloride to ensure that the alloying between the elements during the magnesothermic reduction reaction is met by controlling the addition mass of the raw materials ammonium paratungstate, ammonium molybdate, tantalum chloride, and niobium chloride to meet the condition of 4.2[ammonium paratungstate] + 1.3[ammonium molybdate] = (3.4~8.3)([tantalum chloride] + [niobium chloride]). This ensures the alloying between the elements during the magnesothermic reduction reaction, and the resulting nanoscale refractory high-entropy alloy powder has a single phase of WMoTaNb alloy, rather than being a composite powder formed solely through physical interactions.

[0022] 3. This invention controls the addition of magnesium powder and sodium chloride during the magnesian reduction reaction, causing the chemically active magnesium powder to undergo a displacement reaction with tungsten-molybdenum composite oxide powder and tantalum-niobium composite oxide powder. This reduces the metal elements from their oxide form to their elemental form. Since the magnesian reduction reaction is exothermic, the released heat causes the tungsten, molybdenum, tantalum, and niobium elemental powders to alloy and form WMoTaNb refractory high-entropy alloy powder. At the same time, the sodium chloride melts to form a molten salt pool, absorbing the heat released by the magnesian reduction reaction. This allows for precise control of the temperature of the magnesian reduction reaction, ensuring that the tungsten-molybdenum composite oxide powder and tantalum-niobium composite oxide powder are fully reduced, ultimately obtaining nanoscale refractory high-entropy alloy powder.

[0023] 4. By limiting the temperature of the magnesian reduction reaction to 1000℃~1200℃, the tungsten-molybdenum composite oxide powder and tantalum-niobium composite oxide powder are fully reduced, and the metal elements are further diffused and homogenized to obtain a single-phase structure of WMoTaNb alloy.

[0024] 5. The nanoscale refractory high entropy alloy powder prepared by this invention has a particle size of 10nm to 180nm and an average particle size of 30nm to 80nm. It has high sintering activity, and the products prepared by sintering with it as raw material have advantages such as ultrafine grains and high performance, and have good application prospects.

[0025] 6. The preparation method of the present invention is simple, easy to implement, has a short process, and low cost.

[0026] The technical solution of the present invention will be further described in detail below through embodiments. Detailed Implementation

[0027] Example 1

[0028] This embodiment includes the following steps:

[0029] Step 1: Preparation of tungsten-molybdenum precursor powder: Under the condition of electromagnetic stirring in a water bath at 60℃, 10g of ammonium paratungstate and 19g of ammonium molybdate were dissolved in 270mL of deionized water to obtain a mixed solution. Then, strong acid was added to the mixed solution until precipitation was complete. After removing the supernatant, the solution was dried to obtain tungsten-molybdenum precursor powder.

[0030] Step 2: Preparation of tantalum-niobium precursor powder: Under electromagnetic stirring in a water bath at 60°C, 4.3g of tantalum chloride and 7.2g of niobium chloride were simultaneously dissolved in 100mL of anhydrous ethanol to obtain a mixed solution. Then, ammonia was added to the mixed solution until precipitation was complete. After removing the supernatant, the solution was dried to obtain tantalum-niobium precursor powder.

[0031] Step 3: Preparation of tungsten-molybdenum composite oxide powder: The tungsten-molybdenum precursor powder prepared in Step 1 is heated to 350℃ in air atmosphere and held for 2.5h before furnace cooling to obtain tungsten-molybdenum composite oxide powder.

[0032] Step 4: Preparation of tantalum-niobium composite oxide powder: The tantalum-niobium precursor powder prepared in step 2 is heated to 910℃ in air atmosphere and held for 3 hours, then furnace cooled to obtain tantalum-niobium composite oxide powder.

[0033] Step 5, Magnesium reduction reaction: The tungsten-molybdenum composite oxide powder prepared in Step 3 and the tantalum-niobium composite oxide powder prepared in Step 4 are uniformly mixed with magnesium powder and sodium chloride. The mixture is heated to 1100℃ under argon atmosphere and held for 5 hours for magnesium reduction reaction, followed by furnace cooling. The mass of magnesium powder is 5.2 times the total mass of the tungsten-molybdenum composite oxide powder and the tantalum-niobium composite oxide powder, and the mass of sodium chloride is 1.6 times the mass of magnesium powder. The product is then dissolved in strong acid and allowed to settle and precipitate. After removing the supernatant, the product is dried to obtain nano-sized WMoTaNb refractory high-entropy alloy powder.

[0034] Testing revealed that the nanoscale WMoTaNb refractory high-entropy alloy powder prepared in this embodiment has a particle size of 13nm to 172nm, an average particle size of 35nm, and a microstructure of WMoTaNb alloy single phase, with atomic percentages of W, Mo, Ta, and Nb of 25.3%, 24.7%, 25.6%, and 24.4%, respectively.

[0035] Example 2

[0036] The difference between this embodiment and Embodiment 1 is that in step one, 6g of ammonium paratungstate and 12g of ammonium molybdate are dissolved simultaneously in 140mL of deionized water; in step two, 1.6g of tantalum chloride and 3.8g of niobium chloride are dissolved simultaneously in 60mL of anhydrous ethanol.

[0037] Testing revealed that the nanoscale WMoTaNb refractory high-entropy alloy powder prepared in this embodiment has a particle size of 16nm to 162nm, an average particle size of 43nm, and a microstructure of WMoTaNb alloy single phase, with atomic percentages of W, Mo, Ta, and Nb of 22.5%, 59.3%, 8.1%, and 10.1%, respectively.

[0038] Example 3

[0039] The difference between this embodiment and Embodiment 1 is that in step five, the temperature is raised to 1180°C and held for 3 hours to carry out the magnesium thermoreduction reaction.

[0040] Testing revealed that the nanoscale WMoTaNb refractory high-entropy alloy powder prepared in this embodiment has a particle size of 12nm to 177nm, an average particle size of 78nm, and a microstructure of WMoTaNb alloy single phase, with atomic percentages of W, Mo, Ta, and Nb of 25.5%, 29.2%, 34.7%, and 10.6%, respectively.

[0041] Example 4

[0042] The difference between this embodiment and Embodiment 1 is as follows: in step one, 5.2g of ammonium paratungstate and 5.2g of ammonium molybdate are simultaneously dissolved in 130mL of deionized water to obtain a mixed solution; in step two, 2.1g of tantalum chloride and 1.9g of niobium chloride are simultaneously dissolved in 50mL of anhydrous ethanol to obtain a mixed solution.

[0043] Testing revealed that the nanoscale WMoTaNb refractory high-entropy alloy powder prepared in this embodiment has a particle size of 16nm to 122nm, an average particle size of 64nm, and a microstructure of WMoTaNb alloy single phase. The atomic percentages of W, Mo, Ta, and Nb are 24.2%, 31.6%, 26.3%, and 17.9%, respectively.

[0044] Example 5

[0045] The difference between this embodiment and Embodiment 1 is as follows: in step one, 19.7g of ammonium paratungstate and 19.7g of ammonium molybdate are simultaneously dissolved in 280mL of deionized water to obtain a mixed solution; in step two, 9.9g of tantalum chloride and 9.9g of niobium chloride are simultaneously dissolved in 110mL of anhydrous ethanol to obtain a mixed solution.

[0046] Testing revealed that the nanoscale WMoTaNb refractory high-entropy alloy powder prepared in this embodiment has a particle size of 26 nm to 172 nm, an average particle size of 71 nm, and a microstructure of WMoTaNb alloy single phase. The atomic percentages of W, Mo, Ta, and Nb are 24.3%, 34.6%, 26.3%, and 14.8%, respectively.

[0047] Example 6

[0048] The difference between this embodiment and Embodiment 1 is as follows: in step one, 2.4g of ammonium paratungstate and 1.6g of ammonium molybdate are dissolved simultaneously in 280mL of deionized water to obtain a mixed solution; in step two, 1.2g of tantalum chloride and 1.2g of niobium chloride are dissolved simultaneously in 50mL of anhydrous ethanol to obtain a mixed solution.

[0049] The nanoscale WMoTaNb refractory high-entropy alloy powder prepared in this embodiment has a particle size of 21 nm to 176 nm, an average particle size of 73 nm, and a single phase structure of WMoTaNb alloy. The atomic percentages of W, Mo, Ta, and Nb are 22.1%, 34.6%, 28.5%, and 14.8%, respectively.

[0050] Example 7

[0051] The difference between this embodiment and Embodiment 1 is that in step three, the tungsten-molybdenum precursor powder is heated to 220°C in air and held for 0.6 hours before being furnace cooled; in step four, the tantalum-niobium precursor powder is heated to 710°C in air and held for 0.7 hours before being furnace cooled.

[0052] Testing revealed that the nanoscale WMoTaNb refractory high-entropy alloy powder prepared in this embodiment has a particle size of 19 nm to 156 nm, an average particle size of 32 nm, and a microstructure of WMoTaNb alloy single phase, with atomic percentages of W, Mo, Ta, and Nb of 32.3%, 44.7%, 8.1%, and 14.9%, respectively.

[0053] Example 8

[0054] The difference between this embodiment and Embodiment 1 is that in step three, the tungsten-molybdenum precursor powder is heated to 580°C in air and held for 4.8 hours before being furnace cooled; in step four, the tantalum-niobium precursor powder is heated to 980°C in air and held for 4.9 hours before being furnace cooled.

[0055] Testing revealed that the nanoscale WMoTaNb refractory high-entropy alloy powder prepared in this embodiment has a particle size of 19 nm to 137 nm, an average particle size of 3 nm, and a microstructure of WMoTaNb alloy single phase, with atomic percentages of W, Mo, Ta, and Nb of 59.0%, 24.7%, 8.1%, and 8.2%, respectively.

[0056] Example 9

[0057] The difference between this embodiment and Embodiment 1 is that in step five, the mass of magnesium powder is 10.8 times the total mass of tungsten-molybdenum composite oxide powder and tantalum-niobium composite oxide powder, and the mass of sodium chloride is 4.4 times the mass of magnesium powder.

[0058] Testing revealed that the nanoscale WMoTaNb refractory high-entropy alloy powder prepared in this embodiment has a particle size of 11 nm to 144 nm, an average particle size of 42 nm, and a microstructure of WMoTaNb alloy single phase, with atomic percentages of W, Mo, Ta, and Nb of 25.5%, 58.1%, 8.3%, and 8.1%, respectively.

[0059] Example 10

[0060] The difference between this embodiment and Embodiment 1 is that in step five, the magnesium thermoreduction reaction is carried out by heating to 1030°C under argon atmosphere and holding for 2.3 hours, followed by furnace cooling.

[0061] Testing revealed that the nanoscale WMoTaNb refractory high-entropy alloy powder prepared in this embodiment has a particle size of 10 nm to 161 nm, an average particle size of 55 nm, and a microstructure of WMoTaNb alloy single phase, with atomic percentages of W, Mo, Ta, and Nb of 20.6%, 36.6%, 34.6%, and 8.2%, respectively.

[0062] Example 11

[0063] The difference between this embodiment and Embodiment 1 is that in step five, the magnesium thermoreduction reaction is carried out by heating to 1180°C under argon atmosphere and holding for 7.7 hours, followed by furnace cooling.

[0064] The nanoscale WMoTaNb refractory high-entropy alloy powder prepared in this embodiment has a particle size of 13nm to 177nm, an average particle size of 39nm, and a microstructure of WMoTaNb alloy single phase. The atomic percentages of W, Mo, Ta, and Nb are 24.8%, 20.5%, 30.0%, and 34.7%, respectively.

[0065] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any way. Any simple modifications, alterations, and equivalent changes made to the above embodiments based on the inventive essence shall still fall within the protection scope of the present invention.

Claims

1. A method for preparing nanoscale refractory high-entropy alloy powder, characterized in that, The method includes the following steps: Step 1: Preparation of tungsten-molybdenum precursor powder: Under the condition of electromagnetic stirring in a water bath, ammonium paratungstate and ammonium molybdate are dissolved simultaneously in deionized water to obtain a mixed solution. Then, strong acid is added to the mixed solution until precipitation is complete. After removing the supernatant, the solution is dried to obtain tungsten-molybdenum precursor powder. Step 2: Preparation of tantalum-niobium precursor powder: Under the condition of electromagnetic stirring in a water bath, tantalum chloride and niobium chloride are dissolved simultaneously in anhydrous ethanol to obtain a mixed solution. Then, ammonia water is added to the mixed solution until precipitation is complete. After removing the supernatant, the solution is dried to obtain tantalum-niobium precursor powder. The masses of ammonium paratungstate and ammonium molybdate in step one, and tantalum chloride and niobium chloride in step two, satisfy the following: 4.2[ammonium paratungstate] + 1.3[ammonium molybdate] = (3.4~8.3)([tantalum chloride] + [niobium chloride]); Step 3: Preparation of tungsten-molybdenum composite oxide powder: The tungsten-molybdenum precursor powder prepared in Step 1 is heated and kept at a constant temperature in air and then cooled in a furnace to obtain tungsten-molybdenum composite oxide powder. Step 4: Preparation of tantalum-niobium composite oxide powder: The tantalum-niobium precursor powder prepared in step 2 is heated and kept at a constant temperature in air and then furnace cooled to obtain tantalum-niobium composite oxide powder. Step 5, Magnesium reduction reaction: The tungsten-molybdenum composite oxide powder prepared in Step 3 and the tantalum-niobium composite oxide powder prepared in Step 4 are uniformly mixed with magnesium powder and sodium chloride. The mixture is heated and kept at a constant temperature under argon atmosphere to carry out the magnesium reduction reaction. After furnace cooling, the product is dissolved with strong acid and allowed to settle and precipitate. After removing the supernatant, it is dried to obtain nano-sized WMoTaNb refractory high-entropy alloy powder. The magnesium reduction reaction is carried out at 1000℃~1200℃ for 2h~8h.

2. The method for preparing nanoscale refractory high-entropy alloy powder according to claim 1, characterized in that, In step one, the temperature of the water bath electromagnetic stirring condition is 60℃, and the mixed solution is prepared according to the ratio of 5g~20g ammonium paratungstate and 5g~20g ammonium molybdate dissolved in 130mL~280mL deionized water. In step two, the temperature of the water bath electromagnetic stirring condition is 60℃, and the mixed solution is prepared according to the ratio of 1g~10g tantalum chloride and 1g~10g niobium chloride dissolved in 50mL~110mL anhydrous ethanol.

3. The method for preparing nanoscale refractory high-entropy alloy powder according to claim 1, characterized in that, The heating and heat preservation temperature in step three is 200℃~600℃, and the time is 0.5h~5h; the heating and heat preservation temperature in step four is 700℃~1000℃, and the time is 0.5h~5h.

4. The method for preparing nanoscale refractory high-entropy alloy powder according to claim 1, characterized in that, In step five, the mass of the magnesium powder is 5 to 11 times the total mass of the tungsten-molybdenum composite oxide powder and the tantalum-niobium composite oxide powder, and the mass of the sodium chloride is 1.5 to 4.5 times the mass of the magnesium powder.

5. A nanoscale refractory high-entropy alloy powder prepared by the method described in any one of claims 1 to 4, characterized in that, The nanoscale refractory high-entropy alloy powder has a particle size of 10nm~180nm, an average particle size of 30nm~80nm, and a microstructure of WMoTaNb alloy single phase, with atomic percentages of W, Mo, Ta, and Nb of 20%~60%, 20%~60%, 8%~35%, and 8%~35%, respectively.